The impact of mindfulness on leadership effectiveness in a health care setting: a pilot study. Issue 7 (16th November 2015) - Wasylkiw, Louise; Holton, Judith; Azar, Rima; Cook, William
Abstract : Purpose: – The purpose of this paper is to examine the impact of mindfulness awareness practice (MAP) on mid-level health-care managers' leadership. Design/methodology/approach: – In total, 11 mid-level health-care managers in eastern Canada took part in an intensive weekend retreat and a follow-up webinar on mindfulness awareness. Perceived stress and leadership effectiveness were assessed pre- and post-intervention (i.e. four and eight weeks). A control group ( n =10) also completed the same measures twice. Additionally, informants ( n =28) provided assessments of participants' leadership pre- and post-intervention. Follow-up interviews were carried out with eight participants 12-16 weeks post-intervention. Findings: – In comparison to controls, retreat participants showed significant increases in mindfulness and corresponding decreases in stress that were sustained across eight weeks post-retreat; retreat participants reported significant positive changes in their leadership effectiveness that were corroborated by informants. Qualitative data, however, suggest that sustaining a mindfulness practice presents significant challenges to middle managers in a health care setting. Research limitations/implications: – The findings are useful to management working in health services that are plagued by increasing demands and changes. Despite the small sample and lack of random assignment, the pilot data support the efficacy of MAP in improving leadership. Originality/value: – Little empirical research supports the claim that MAP enhances leadership. The present study employed a mixed methods approach to address this gap and demonstrates the potential benefits of MAP among mid-level managers.